TOBY STRATEGY (YOUR OBESITY LOWER IT NOW) (Fiep Bulletin - online, 2020)
Abstract: The study carried out in 2015 by the Mexican Institute for Competitiveness (IMCO) indicates: 80% of the population is overweight 30% is Obesity.Obesity generates high economic losses and reduces the country's competitiveness:Higher costs to the public treasury to treat associated diseasesLower labor productivityHigher expenses for the population and loss of quality of lifeNational Health and Nutrition Survey ENSANUT 2000 - 2016 points to Yucatán as the first place at the national level in obesity and overweight.The TOBY program develops strategies that promote knowledge and the detection of overweight or obesity problems, as well as alternatives for their treatment, involving family participation.In the first instance, the fundamental idea was to combat obesity by promoting sports in children and instilling in them the follow-up of an adequate diet with the dish of good Mayan eating. The TOBY program visits the elementary schools of the state of Yucatán.